2012
DOI: 10.1645/ge-2689.1
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Community Structure of Tropidurus torquatus (Squamata: Tropiduridae) in a Rocky Outcrop Area of Minas Gerais State, Southeastern Brazil

Abstract: The helminth community of Tropidurus torquatus (Squamata: Tropiduridae) from a rocky outcrop area located in the state of Minas Gerais, southeastern Brazil, was studied. Ninety-two of the 110 individuals examined (83.6%) harbored helminths. Five species were found, including 3 nematodes ( Physaloptera lutzi , Parapharyngodon bainae , and Oswaldofilaria chabaudi ), 1 unidentified cestode species, and 1 acanthocephalan cystacanth also not identified. Only the nematode species had sufficient data to perform ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…The positive correlation between parasite load/SVL and parasite load /SVL/body mass observed in M. arajara was similar to what has been observed in its congeners M. agilis, M. macrorhyncha (Vrcibradic et al 2000), and M. frenata (Vrcibradic et al 1999). It is known that older individuals present greater SVL/body mass when compared to younger animals, thus increasing the chances of acquiring parasites due to greater time for contact with the environment throughout life (Ribas et al 1998a;Pereira et al 2012). In addition, a large body volume provides the parasite an abundance of resources (space to feed) available for colonization (Aho 1990;Van Sluys et al 1994;Poulin 1997), even more so if we consider that M. arajara has a large body size among lizards of the genus Mabuya (Ribeiro et al 2015).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The positive correlation between parasite load/SVL and parasite load /SVL/body mass observed in M. arajara was similar to what has been observed in its congeners M. agilis, M. macrorhyncha (Vrcibradic et al 2000), and M. frenata (Vrcibradic et al 1999). It is known that older individuals present greater SVL/body mass when compared to younger animals, thus increasing the chances of acquiring parasites due to greater time for contact with the environment throughout life (Ribas et al 1998a;Pereira et al 2012). In addition, a large body volume provides the parasite an abundance of resources (space to feed) available for colonization (Aho 1990;Van Sluys et al 1994;Poulin 1997), even more so if we consider that M. arajara has a large body size among lizards of the genus Mabuya (Ribeiro et al 2015).…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, during the rainy season, parasite eggs may be carried away by rain, providing less direct contact between hosts and parasites. This phenomenon is known to influence infection rates in Tropidurus torquatus (Pereira et al 2012). The increased infection rates may also be related to physiological mechanisms in these animals, such as energy imbalance and hormonal changes (Aho 1990;Marcogliese 2004;Roberts et al 2004;Martin et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body size of the host is clearly one of the main influences in parasite populations (Poulin, 2004;Kamiya et al, 2014). Other studies with Tropidurus lizards found a positive relationship between body size and the intensity of parasite infection (Anjos et al, 2012;Pereira et al, 2012). Corroborating the island biogeography theory (see MacArthur & Wilson, 1967), the body of the host acts as an island to the parasite species.…”
Section: Discussionmentioning
confidence: 94%
“…Male lizards in the Restinga and Atlantic Forest areas might show higher levels of helminth abundance caused by some of these factors, such as high testosterone concentrations and the stress caused by fighting for territory (Schall & Dearing, 1987;Salvador et al, 1996). Males of T. hispidus are known for their territorial behaviour, but some differences in helminth species abundance between males and females can also be related to diet, sexual dimorphism and differences in habitat use by each sex (Aho, 1990;Fontes et al, 2003;Pereira et al, 2012). The comparison between the proportion of reproductive individuals per month and helminth prevalence was statistically significant in Caatinga.…”
Section: Discussionmentioning
confidence: 99%